Managing a confirmed or suspected COVID-19 case: a guide for sports - Rankin, A.; Heron, N. (British Journal of Sports Medicine, 2021)
COVID-19 had, and continues to have, a significant impact on the 2020 sporting calendar, with the summer Tokyo Olympics postponed until 2021 and cancellation of a number of other sporting events and tournaments. Athletes and their sports are now slowly returning to a `new normal` during this COVID-19 pandemic, and as athletes return to their sport in the coming months, we are expecting to see a number of athletes who develop suspected COVID-19 symptoms or indeed test positive for COVID-19. In our roles at sporting facilities/sports organisations, what is our responsibility to both the athlete with suspected COVID-19 symptoms and/or who test positive for COVID-19 as well as the other athletes and staff working within this environment?